HIDROGENASI MINYAK KELAPA SAWIT RENDAH LEMAK TRANS DALAM REAKTOR BATCH (Hidrogenation of Palm oil for Low Trans Fatty Acid in a Batch Reactor) - Rahmi, Dwinna (Baristand Industri Banda Aceh, 2016)
Optimize hidrogenation of palm oil hidrogenated low trans fatty acid has performed in a batchreactor with various speed agitation, pressure and time process. Trans fatty acid content could incearesingLDL and reducing HDL in the blood therefore risk for heart disease. In this reasearch, the optimum processwas 500 rpm for agitation speed, pressure 70 bar and time process 60 minutes. The result showed trans fattyacid is zero (0), iodine value less than 1 g/100g and melting point more than 50 oC. The SFC of the productwere 91% at temperature 10 oC, 64% at temperature 20 oC, 28% at temperature 30 oC, 19% at temperature 40oC, 8% at temperature 50 oC, dan 0% at temperature 60 oC.